Is C-type natriuretic peptide regulated by a feedback loop? A study on systemic and local autoregulatory effect. - Yohei Ueda; Keisho Hirota; Ichiro Yamauchi; Takuro Hakata; Takafumi Yamashita; Toshihito Fujii; Akihiro Yasoda; Nobuya Inagaki (PLoS ONE, 2020)
C-type natriuretic peptide (CNP) is a pivotal enhancer of endochondral bone growth and is expected to be a therapeutic reagent for impaired skeletal growth. Although we showed that CNP stimulates bone growth as a local regulator in the growth plate via the autocrine/paracrine system, CNP is abundantly produced in other various tissues and its blood concentration is reported to correlate positively with growth velocity. Therefore we investigated the systemic regulation of CNP levels using rodent models. In order to examine whether CNP undergoes systemic feedback regulation, we investigated blood CNP levels and local CNP expression in various tissues, including cartilage, of 4-week-old rats after systemic administration of sufficient amounts of exogenous CNP (0.5 mg/kg/day) for 3 days. This CNP administration did not alter blood NT-proCNP levels in male rats but decreased mRNA expression only in tissue that included cartilage. Decrease in expression and blood NT-proCNP were greater in female rats. To analyze the existence of direct autoregulation of CNP in the periphery as an autocrine/paracrine system, we estimated the effect of exogenous supplementation of CNP on the expression of endogenous CNP itself in the growth plate cartilage of extracted fetal murine tibias and in ATDC5, a chondrogenic cell line. We found no alteration of endogenous CNP expression after incubation with adequate concentrations of exogenous CNP for 4 and 24 hours, which were chosen to observe primary and later transcriptional effects, respectively. These results indicate that CNP is not directly autoregulated but indirectly autoregulated in cartilage tissue. A feedback system is crucial for homeostatic regulation and further studies are needed to elucidate the regulatory system of CNP production and function.